Analysis of cracked bars with rectangular cross-section and isotropic coating layer under torsion. (August 2017) - Hassani, A.R.; Monfared, M.M.
Abstract: The solution to problem of a Volterra-type screw dislocation in a rectangular cross section bar with an isotropic coating is first achieved by means of a finite Fourier cosine transform. The bar is under axial torque which is governed by Saint-Venant torsion theory. The series solution is then derived for warping function and stress fields in the rectangular cross section with an isotropic coating. The dislocation solution is employed to derive a set of Cauchy singular integral equations for the analysis of smooth cracks. The solution of these equations is used to determine the torsional rigidity of bar and the stress intensity factors for the crack tips. Finally, several examples are presented to show the accuracy and efficiency of the dislocation technique in Saint-Venant torsion problems. Graphical abstract: Highlights: We analyze the torsion problem of a rectangular bar with an isotropic coating containing a screw dislocation. The bar and its coating are governed by the Saint-Venant torsion theory. We use the dislocation distribution technique for analysis of multiple arbitrary oriented curved cracks. We rewrite the solution of problem in term of new functions which converge very rapidly.